Exploring the Use of Procedural Policy Instruments in the Development and Implementation of French Second Language Policy in New Brunswick and Nova Scotia - Mitchell, Sara (Université d'Ottawa / University of Ottawa, 2016)
From 2006-2008, both New Brunswick and Nova Scotia proposed changes to their French second language (FSL) policies and programs. In observing the cases, it becomes clear that government officials made use of policy instruments to both implement policy and navigated the policy process. This work builds off existing literature that seeks to understand the instrument selection process, as well as the impact of policy tools on the policy-making process and more specifically, on the actors involved directly and indirectly in it. Using a framework that incorporates components of Contextual Interaction Theory and elements of procedural policy instrument scholarship, the project endeavours to identify what instruments were used to develop and implement FSL policy in New Brunswick and Nova Scotia, as well as to comprehend why the tools were selected. The dissertation relies on document analysis and semi-structured interviews conducted with government officials and stakeholders to determine that instrument selection is based on the actors’ cognitions, motivations, and available/accessible resources. Furthermore, legitimacy plays an integral role in the selection of instruments. Government policymakers are faced with varying degrees of legitimacy, as expressed by actors indirectly involved in the policy process. Inevitably, these actors react to policy content and the policy process, which leads to sometimes contentious interactions. The current research expands on the educational policy literature by using a lens that accounts for the role of instruments in the policy process and provides a nuanced understanding of how the actors’ interactions shape and influence policy-making. It makes an original contribution to the policy instruments literature by developing a framework that accounts for the selection criteria used by both policymakers and stakeholders when choosing policy tools and resources. This dissertation contributes to the discipline of public administration and the field of public policy primarily by expounding the explanatory value of policy instruments regarding what they can tell us about the policy process, policy-making and policy outcomes. It does this by looking at how it is actors both directly and indirectly involved in the policy process interpret policy instruments and shows how government’s policy-making capacity is constrained not only by the resources available to it but by the resources accessible to actors indirectly involved in the policy process. Looking at the reciprocal nature of tool selection and tool implementation helps to explain policy-making and outcomes, as well as accounts for the roles of actors both proximately and peripherally involved in the process.
Keywords: Public policy; languages in education policy; educational policy; French second language policy; policy instruments; eastern Canada